Modeling and analysis of the mechanical anisotropy of Hastelloy X alloy fabricated by laser powder bed fusion - Ruolin Li; Liang Cheng; Ji Liu; Yunlong Zhang; Sai Li; Jie Bai; Rui Ma (Journal of Materials Research and Technology)
In this work, the mechanical properties of the laser powder bed fused Hastelloy X alloy was studied by means of tension tests along and perpendicular to the building direction. The results showed that the as-built materials exhibited a <001> fiber component with a maximum texture strength of ∼2.4. Meanwhile, the alloy showed a quite strong mechanical anisotropy such that the flow strength perpendicular to building direction was much higher than that along building direction by ∼100 MPa. By using the viscous-plasticity self-consistent (VPSC) method, it was demonstrated that such a large stress deviation cannot be ascribed to the weak texture. Meanwhile, considering the large aspect ratio of the columnar grains, a modified VPSC model was developed by taken the so-called phenomenological Hall-Petch relation into account, which was capable of accurately capturing the strong mechanical anisotropy of the present alloy. The modified VPSC model, which was calibrated to both the mechanical data and texture evolution during tension tests, was applied for virtual material testing along various tensile directions within the anisotropy plane of the material, whereby the advanced yield function Yld2004-18p was calibrated through the genetic algorithm. It was found that the Yld2004-18p yield function can accurately describe both the strength anisotropy and flow anisotropy of the material, whereby the initial and subsequent yield surfaces were generated for the LPBF Hastelloy X alloy.